For a reparatory social science - Bhambra Gurminder K. (Global Social Challenges Journal, 2022)
The continuing coronavirus pandemic has combined with other global crises to highlight some of the fundamental challenges of inequality that currently face us. They are global both in their current configuration and their historical constitution. Similarly, any solutions to the challenges represented will be global. The continuing relevance of the social sciences will rest on their ability adequately to conceptualise the global processes involved. It is only by acknowledging the significance of the ‘colonial global’ that it will be possible to understand and address the necessarily postcolonial present that is the context for issues of inequality in the present. This article argues for the need to consider our colonial past as the basis for thinking about contemporary configurations of the global. This is followed by an address of the implications of these arguments for how we understand citizenship and belonging in the present. What is needed is a ‘reparatory social science’ committed to undoing the inadequacies that have become lodged in our disciplines and working towards a project of repair and transformation for a world that works for all of us.